Pengaruh Kepemilikan Institusional dan Profitabilitas terhadap Audit Delay - Krisnawati, Titin; Elly, Mohammad Iskak (Ecobuss, 2024)
This research aims to determine the negative influence between institutional ownership and profitability on audit delays in technology companies listed on the Indonesian stock exchange in 2020-2022. So that the delivery of company financial reports will no longer occur delays or delays. The research has a population of 44 technology companies listed on the Indonesian Stock Exchange in 2020-2022 with a total sample of 21 companies obtained from the purposive sampling method then multiplied by 3 periods to become 63 samples of technology companies that will be analyzed. The research method uses quantitative with a causal associative explanation level with SEM-PLS data analysis using Smart PLS 3.0 software. The results of this research are that the institutional ownership variable has no influence on audit delay in technology companies listed on the Indonesian Stock Exchange in 2020-2022. Meanwhile, the profitability variable has a negative influence on audit delay in technology companies listed on the Indonesian Stock Exchange in 2020-2022.